The influence of price, e-service quality, and brand image on online purchasing decisions - Sahar, Rahmanwali (Universitas Ahmad Dahlan, 2024)
Purpose-Technological advances have now penetrated various sectors of life, including online buying and selling transactions. This provides convenience to consumers because they can make product purchases from anywhere and anytime. Many supporting factors influence consumer decisions when making online purchases. This study aims to analyze the effect of price factors, electronic service quality, and brand image on online purchasing decisions. Design/Methodology/Approach-This study analyzes online purchasing decisions for cosmetics consumers in Asia. Sampling in this study used a cluster random sampling technique, where respondents in certain areas could become research respondents, and 137 respondents were obtained. The data collection method uses a questionnaire distributed online. Then, the analytical tool used is Smart PLS with the bootstrapping process. Findings-The results prove that the three factors analyzed are proven to have a positive effect on online purchasing decisions. Based on these results, producers must pay attention to price, e-service quality, and brand image factors to encourage an increase in the number of consumer purchases. Because transactions are carried out online, there are many factors that consumers consider before making a purchase, including the three factors examined in this study. Research limitations/implications-The limitation of this study is that the number of respondents still needs to be more minimalist in number. In addition, the respondents do not represent every country in the Asian region. This makes the results of this study unable to describe the picture of consumers in Asia making online purchase decisions. The object of research is also still classified as general, namely cosmetic consumers, not mentioning a particular brand so that it can be more specific. Originality/value-This research is still very minimal conducted by previous researchers who use the object of cosmetic consumers in the Asian region. Generally, previous studies used different objects or in a country.